The Effects of Low Doses of Two Fusarium Toxins, Zearalenone and Deoxynivalenol, on the Pig Jejunum. A Light and Electron Microscopic Study - Przybylska-Gornowicz, Barbara (Toxins (Basel), 2015)
Immature gilts were administered per os with zearalenone (ZEN) at 40 μg/kg BW (group Z, n = 9), deoxynivalenol (DON) at 12 μg/kg BW (group D, n = 9), a mixture of ZEN and DON (group M, n = 9) or a placebo (group C, n = 9) over a period of six weeks. The pigs were sacrificed after one, three, or six weeks of the treatment (12 pigs per each time-point). Histological investigations revealed an increase in the mucosal thickness and the crypt depth as well as a decrease in the ratio of the villus height to the crypt depth in groups D and M after six weeks of exposure to the mycotoxins. The number of goblet cells in the villus epithelium was elevated in groups Z and M after one week and in group D after three weeks. The administration of ZEN increased the lymphocyte number in the villus epithelium after 1 week and the plasma cell quantity in the lamina propria after one, three, and six weeks of the experiment. DON treatment resulted in an increase in the lymphocyte number in the villus epithelium and the lamina propria after six weeks, and in the plasma cell quantity in the lamina propria after one, three, and six weeks of exposure. In group M, lymphocyte counts in the epithelium and the lamina propria increased significantly after six weeks. Neither mycotoxin induced significant adverse changes in the ultrastructure of the mucosal epithelium and the lamina propria or in the intestinal barrier permeability. Our results indicate that immune cells are the principal target of low doses of ZEN and DON.